What is the best therapy for anal fissures?. Issue 12 (December 2017) - Seferovic, Admir; Pippin, Philip; Wortz, Kathryn
Abstract : EVIDENCE‐BASED ANSWER : Surgical management is consistently superior to topical diltiazem or glyceryl trinitrate for chronic anal fissure (SOR: A, systematic review and meta‐analysis) and perhaps also for acute anal fissure (SOR: C, small cohort study). Among medical therapies, diltiazem 2% ointment and glyceryl trinitrate 0.2% ointment are equally effective, but diltiazem has a 30% lower recurrence rate and a 60% lower incidence of headache (SOR: A, systematic review of RCTs).